The spin states of cobalt ions and thermo-e.m.f. in erbium and holmium cobaltites - Khirnyi, V.F.; Kozlovskii, A.A.; Semenov, A.V.; Puzikov, V.M. (Functional Materials, 2009)
The temperature dependences of thermo-e.m.f. for Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓSrxCoO₃₋δ, Er₁₋ₓCaxCoO₃₋δ, Ho₁₋ₓCaxCoO₃₋δ ceramics have been studied in the temperature range of 300 K (of 100 K for some materials) to 600 K. The Zeebeck coefficient for Sr doped samples is lowered as the strontium content increases and the temperature rises. It has been shown that the 3d level splitting and the charge disproportionation of cobalt ions is to be taken into account to explain the above-mentioned behavior. Досліджено температурні залежності термо-ЕРС керамік Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓSrxCoO₃₋δ, Er₁₋ₓCaxCoO₃₋δ та Ho₁₋ₓCaxCoO₃₋δ в області температур від 300 К (для деяких від 100 К) до 600 К. Коефіцієнт 3еєбека Sr-легованих зразків знижується при зростанні вмісту стронцію та температури. Показано, що для пояснення такої поведінки необхідно враховувати розщеплення 3d-рівнів та зарядову диспропорціоналізацію іонів кобальту. Исследованы температурные зависимости термо-ЭДС керамик Er₁₋ₓSrₓCoO₃₋δ, Ho₁₋ₓSrxCoO₃₋δ, Er₁₋ₓCaxCoO₃₋δ, Ho₁₋ₓCaxCoO₃₋δ в области температур от 300 К (для некоторых от 100 К) до 600 К. Коэффициент 3еебека Sr-легированных образцов понижается при увеличении содержания стронция и температуры. Показано, что для объяснения такого поведения необходимо учитывать расщепление 3d-уровней и зарядовую диспропорционализацию ионов кобальта.